Analisis Pengaruh Kualitas Layanan Terhadap Kepuasan Nasabah (Studi pada BANK BRI KC. Semarang Pandanaran) - Pati Ritan, Patrianus (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to examine the influence of service quality dimensions tangibles, reliability, responsiveness, assurance, and empathy on customer satisfaction at Bank BRI Pandanaran Branch in Semarang. The research integrates service quality theory and the Service-Dominant Logic (SDL) approach as its theoretical foundation. Service quality theory assesses how well the services provided meet customer expectations, while SDL emphasizes that service value is co-created through interaction and collaboration between companies and customers. A quantitative method was employed, using a sample of 41 respondents who are offline customers at BRI Pandanaran. Data were analyzed using multiple linear regression. The results show that overall service quality has a positive and significant effect on customer satisfaction. However, the tangibles and reliability dimensions were not statistically significant. In contrast, empathy, assurance, and especially responsiveness showed significant impacts. These findings support the SDL perspective, highlighting that active customer involvement, along with speed and accuracy in service delivery, are crucial elements in value co-creation, which directly influence customer satisfaction in the banking sector